2016
DOI: 10.1177/1457496915607410
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Fractures in Alpine Skiing and Snowboarding in Finland: A Retrospective Study on Fracture Types and Injury Mechanisms in 363 Patients

Abstract: Background and Aim: alpine skiing and snowboarding share the hazards of accidents accounting for tibial fractures. The aim of this study was to evaluate the fracture patterns and mechanisms of injury of tibial fractures taking place in downhill skiing and snowboarding.Materials and methods: all patients with tibial fracture due to alpine skiing or snowboarding accident treated in four trauma centers next to the largest ski resorts in Finland were analyzed between 2006 and 2012. The hospital records were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
1
20
0
1
Order By: Relevance
“… 28 Stenroos et al found tibial plateau fractures slightly more likely than tibia-shaft fractures in snowboarders. 43 Snowboarders were also more likely than skiers to suffer complex periarticular fractures. 43 Complex proximal tibia fractures have been associated with high energy and axial pressure with rotational forces, often associated with loss of control while jumping with hard snowboard boots.…”
Section: Lower Extremitymentioning
confidence: 98%
See 1 more Smart Citation
“… 28 Stenroos et al found tibial plateau fractures slightly more likely than tibia-shaft fractures in snowboarders. 43 Snowboarders were also more likely than skiers to suffer complex periarticular fractures. 43 Complex proximal tibia fractures have been associated with high energy and axial pressure with rotational forces, often associated with loss of control while jumping with hard snowboard boots.…”
Section: Lower Extremitymentioning
confidence: 98%
“…In a retrospective study of 363 skiers and snowboarders suffering tibial fractures over a 7-year period, only 8% of the tibial fractures occurred in snowboarders. 43 Ishimaru et al showed that tibia-shaft fractures accounted for 42% of all lower-leg fractures in their series of snowboarding injuries. 28 Similar to skiers, hard snowboard boots place snowboarders at risk for fractures of the fibula and tibia at the top of the boot, known as a boot-top fracture.…”
Section: Lower Extremitymentioning
confidence: 99%
“…The aforementioned boot top fracture findings led to an alteration of ski boots' safety bindings, and the ski boot was made more flexible in order to reduce the incidence of boot top fractures [ 10 , 13 , 14 ]. Although these adjustments caused a reduced number of overall ankle and tibia fractures, the point of injury moved proximally resulting in an increased number of knee injuries and proximal tibia fractures [ 15 17 ]. Additionally, the recent use of carving skis has been associated with a rise in knee injuries, especially in female athletes, when bindings have not been recently adjusted [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the study was the problems of drawing conclusions based on laboratory tests when compared to real skiing situations where numerous factors may play a role and very different injury mechanisms are possible [6,18,[25][26][27]. Nevertheless, a state-of-the-art measuring and testing device at an experienced and certified test house was employed for the experiment to ensure reliable and valid measurements.…”
Section: Discussionmentioning
confidence: 99%